1980
DOI: 10.1002/1097-0142(19800701)46:1<139::aid-cncr2820460122>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of serum lactate dehydrogenase in malignant lymphoma

Abstract: The pretreatment serum lactate dehydrogenase level (LDH) was the single most important prognostic variable in 30 patients with diffuse histiocytic lymphoma treated between January 1973 and January 1977 with a poly-drug chemotherapy program called the cyclophosphamide L2 protocol at the Memorial Sloan-Kettering Cancer Center. A highly significant difference was found between the survival patterns of patients with LDH levels of 500 U or less and those with LDH levels greater than 500 U. (Two-year survival rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

1982
1982
2001
2001

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 128 publications
(29 citation statements)
references
References 12 publications
3
26
0
Order By: Relevance
“…Consistent with our data, serum LDH has previously been shown to be one of the strongest predictors of prognosis along with age (31,40). Elevated LDH levels in lymphoma have been considered a manifestation of high growth rate or bulky disease (16).…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with our data, serum LDH has previously been shown to be one of the strongest predictors of prognosis along with age (31,40). Elevated LDH levels in lymphoma have been considered a manifestation of high growth rate or bulky disease (16).…”
Section: Discussionsupporting
confidence: 90%
“…The prognostic value of the Ann Arbor distinction between stage III and IV disease remains uncertain. Several studies have reported similar survival figures for stage III and stage IV patients (Koziner et al, 1982;Jagganath et al, 1985;Todd et al, 1986;Laurence et al, 1982;Sweet et al, 1980), but Nathwani et al (1982) (Bierman et al, 1957;Ferraris et al, 1979;Jagannath et al, 1986;Schneider et al, 1980;Hagberg & Siegbahm, 1983). In this study, although serum LDH was shown to be an independent (Christensson et al, 1986;Morgan et al, 1986;Juneja et al, 1986), but few have investigated the prognostic significance of DNA content within the category of high grade lymphoma.…”
Section: Overall Survivalmentioning
confidence: 85%
“…Elevations of serum LDH have major significance in the prognosis of patients with lymphoma and leukemia, in which LDH levels are thought to reflect tumor burden and proliferative activity [33][34][35][36]. In the cases of myeloma with elevated serum LDH, it is hypothesized that a subpopulation of myeloma cells with high LDH content, which are resistant to chemotherapy, exists earlier in the disease course and that such chemotherapy-resistant cells would account for the early relapse and short survival of these patients [6,7].…”
Section: Discussionmentioning
confidence: 99%